Serum uric acid predicts vascular complications in adults with type 1 diabetes: the coronary artery calcification in type 1 diabetes study - Bjornstad, Petter; Maahs, David M.; Rivard, Christopher J.; Pyle, Laura; Rewers, Marian; Johnson, Richard J.; Snell-Bergeon, Janet K. (Acta diabetologica, 2014)
Epidemiologic evidence supports a link between serum uric acid (SUA) and vascular complications in diabetes, but it remains unclear whether SUA improves the ability of conventional risk factor to predict complications. We hypothesized that SUA at baseline would independently predict the development of vascular complications over 6 years and that the addition of SUA to American Diabetes Association’s ABC risk factors (HbA1c, BP, LDL-C) would improve vascular complication prediction over 6 years in adults with type 1 diabetes. Study participants ( N = 652) were 19–56 year old at baseline and re-examined 6 years later. Diabetic nephropathy was defined as incident albuminuria or rapid GFR decline (>3.3 %/year) estimated by the CKD-EPI cystatin C. Diabetic retinopathy (DR) was based on self-reported history, and proliferative diabetic retinopathy (PDR) was defined as laser eye therapy; coronary artery calcium (CAC) was measured using electron-beam computed tomography. Progression of CAC (CACp) was defined as a change in the square-root-transformed CAC volume ≥2.5. Predictors of each complication were examined in stepwise logistic regression with subjects with complications at baseline excluded from analyses. C-statistics, integrated discrimination indices and net-reclassification improvement were utilized for prediction performance analyses. SUA independently predicted development of incident albuminuria (OR 1.8, 95 % CI 1.2–2.7), rapid GFR decline (1.9, 1.1–3.3), DR (1.4, 1.1–1.9), PDR (2.1, 1.4–3.0) and CACp (1.5, 1.1–1.9). SUA improved the discrimination and net-classification risk of vascular complications over 6 years. SUA independently predicted the development of vascular complications in type 1 diabetes and also improved the reclassification of vascular complications.